2002
DOI: 10.1148/radiol.2232010919
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Calcium: Absolute Quantification in Nonenhanced and Contrast-enhanced Multi–Detector Row CT Studies

Abstract: Use of the mass quantification algorithm in combination with a calibration phantom allows accurate quantification of coronary calcium. Measurements of calcium mass obtained at 1.25-mm section width CT angiography have the best agreement with those obtained at the traditional 3-mm section width imaging protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(101 citation statements)
references
References 24 publications
3
94
0
4
Order By: Relevance
“…Moreover, Hong et al [31] found a very high correlation between coronary calcium scores based on 1.25-mm-section-width CT angiography and traditional 3-mm-section-width unenhanced CT. Finally, we did not examine the contribution of intracranial carotid artery calcifications as seen on routine head CT in addition to or in comparison with extracranial carotid calcium burden for the development of symptoms; future studies looking at this relationship would be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Hong et al [31] found a very high correlation between coronary calcium scores based on 1.25-mm-section-width CT angiography and traditional 3-mm-section-width unenhanced CT. Finally, we did not examine the contribution of intracranial carotid artery calcifications as seen on routine head CT in addition to or in comparison with extracranial carotid calcium burden for the development of symptoms; future studies looking at this relationship would be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the baseline measurements included the CAC score determined on CT in addition to other clinical markers 20) . In the MESA study, the prevalence of coronary Several parameters for quantifying the degree of CAC employ measurements of the area and density of all foci of calcification, including the Agatston score 3) , volumetric score 17) and calcium mass score 18) . The Agatston score, the most commonly used tool, is calculated based on the sum of the area and density weightings across the coronary arteries.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Although theoretically better for portability between scanners, this score has not yet undergone sufficient validation (autopsy, histology, outcomes, progression, or angiographic comparison), so its use clinically is premature. 42,43 The retention of the Agatston score has been predicated on the availability of databases for these scores, which include the availability of outcome data so clinicians understand the significance of a certain score. Volume scores are similar, while mass scores tend to be much lower values for a given patient.…”
Section: Coronary Artery Calcified Plaquementioning
confidence: 99%